If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 20 = 3x + 6 Reorder the terms: 20 + x = 3x + 6 Reorder the terms: 20 + x = 6 + 3x Solving 20 + x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 20 + x + -3x = 6 + 3x + -3x Combine like terms: x + -3x = -2x 20 + -2x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 20 + -2x = 6 + 0 20 + -2x = 6 Add '-20' to each side of the equation. 20 + -20 + -2x = 6 + -20 Combine like terms: 20 + -20 = 0 0 + -2x = 6 + -20 -2x = 6 + -20 Combine like terms: 6 + -20 = -14 -2x = -14 Divide each side by '-2'. x = 7 Simplifying x = 7
| 5t^2-7t=60 | | x=2,5/10 | | 1x=1/1 | | 4(2x-1)+8=2x | | (c+o+l+l+e+e+n)*(c+o+l+l+e+e+n)=x | | 5+3G=3+5 | | x+q=q^5+13840934 | | X^4-9X^2-81=0 | | 5x=240 | | -2(2+-2b)+b=8 | | 5h-2=10 | | 4(5x-8)=88 | | -6x-3.4=3x+2.0 | | 6xy(3x^2-4y^2)= | | 4x+3.0=-4x-2.6 | | 4(2s)-3s=15 | | 5x=260 | | -4+-1t-t=2 | | -3s+4s=10 | | r=-3s | | 4p^2-29-20=0 | | 11m=44 | | 7x-2+4=10+5x | | 3x+3+9x-1=6x+12+2x | | (2p+3)(2p-4)=8 | | 4p^2-2p-20=0 | | 7x+16=3x-8 | | 8+6x=28-4x | | 5m+7m= | | 12m+7m= | | x^2-4+2=0 | | (y/14)+(9y/16)=y/20 |